Fatores sócio-político-culturais na formação do professor de matemática: análise em dois contextos de formação - Souza, Roberto Barcelos [UNESP] (2015)
This research aims to discuss significant elements for a rethinking of teachers training involving political, social and cultural factors. Generally, these discussions are insufficient or even nonexistent in teachers training courses and, when it is appear, it is possible to observe that there aren't interrelationships among these factors. What is the potential of continuous teachers training, when assumed the social, political and cultural dimensions as discussions focus in the view of Program Ethnomathematics? This work approaches teachers training from the perspective of Program Ethnomathematics (D'AMBROSIO, 1997, 2001, 2005, 2008), opening ways to teachers put themselves in the process to understand the other and facilitate the dialogue among the different types of knowledge and actions arising from their students and the own specific knowledge structure that was historically constituted. We felt impelled to investigate this issue in order to promote a reflection and a review of the curricula of teacher training courses. The theoretical foundation also uses Inter, Transdisciplinarity and Multiculturalism: Paulo Freire (1987.1996), Edgar Morin (1996, 1990.2000); Souza Santos (2006; 1997) Geertz (1989). The objectives of this research are investigate and highlight social, political and cultural factors, in the view of the teacher training, present in the interrelationships between the two contexts of teachers training, in a perspective of Program Ethnomathematics. In terms of specific objectives: 1) clarify interpretation of the components that drive a sociocultural and political education in undergraduate courses; 2) promote reflections on possible relations between the Program Ethnomathematics and Teachers Training. In accordance with the methodology, it is a qualitative research whose data constitution source focused on two courses offered in graduate studies level. It was necessary use different data instruments. In the case of ...